Pengaruh Motivasi Kerja dan Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan pada Urbanview Hotel One Family Maribaya Lembang - Yogi Sutisna Maulana Putra; Tryiis Arr (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The purpose of this study is to examine how non-physical work environments and work motivation affect employee performance in the hospitality industry. The study uses a quantitative approach, involving the use of observation, interviews, and questionnaires as data collection methods. The research subjects consisted of thirty workers who were selected to be respondents. To ensure the validity of the measuring instruments, the research instruments were tested for validity and reliability. The test results showed that all statements were valid and reliable. The collected data were analyzed using multiple linear regression. The results of the study indicate that the non-physical work environment and work motivation simultaneously have a significant effect on employee performance. This is indicated by a significance value of 0.000 (p < 0.05) and a coefficient of determination (R2) of 0.689. Partially, the non-physical work environment and work motivation also affect employee performance. This study shows that fair salary increases, job satisfaction, the implementation of effective leadership styles, and the creation of a friendly, united, and communicative non-physical work environment increase work motivation in the hospitality industry.